Effects of Practicing Physical Activity During Ramadan Fasting on Health-Related Indices: An Updated Brief Review - Trabelsi, Khaled; Moalla, Wassim; Boukhris, Omar; Ammar, Achraf; Elabed, Kais; Hakim, Ahmed; Chtourou, Hamdi (International Journal of Sport Studies for Health, 2018)
Based on Moon observation, every year, adults healthy Muslims practiced Ramadan intermittent fasting (RIF) for 29 or 30 consecutive days. During RIF Muslims are allowed to food and fluid intake only during night (from sunset to sunrise). Thus, behavioral changes are observed during RIF (e.g., food and sleep habits). Despite these changes, many healthy Muslims maintain their normal habitual physical exercise practice during RIF. However, changes in blood lipids, metabolic markers, electrolytes and hematological parameters during RIF in practitioners of physical activity are yet poorly studied. Therefore, the present review article will summarize the health specific effects of RIF in subjects engaged in physical training during Ramadan.